Pengaruh Pupuk Organik Cair dan Arang Kompos Bioaktif terhadap Pertumbuhan dan Produksi Tanaman Kacang Tanah (Arachis hypogaea L.) - Dedeh Ayu Dahlia; Friza Elinda; Frederika Eliesti (Eduscience Development Journal, 2021)
The study aims to determined the interaction of liquid organic fertilizer and bioactive compost charcoal on peanut plants and to determined the effect of liquid organic fertilizer application on peanut plants and the effect of added bioactive compost charcoal on peanut plants. The research was conducted in Nagari Pasilihan, X Koto Diatas District, Solok Regency in March to June 2021. The design used was the Random Block Design of Factorial (RBDF), the treatment was arranged by a factorial 4 x 3 (12 combination treatments) in 3 repeats. The main factors are the dose of liquid organic fertilizer (A) namely: dose 0 ml / liter (A1), dose 4 ml / liter (A2), dose 6 ml / liter (A3) and dose 8 ml / liter (A4). The second factor is the dose of bioactive compost charcoal (M) which is: dose 100g (M1), dose 200g (M2) and dose 300g (M3). The data was analyzed statistically, and the Duncan New Multiple Range test (DNMRT) is carried out if obtained F calculates the > F table at a real level of 5%. The parameters observed was the height of the plant, the number of flowers, the number of pithy pods, the number of broken pods, the weight of the ground pods and the weight of 100 seeds. The treatment of super bionic POC and bioactive compost charcoal has no effect on crop height, number of damaged pods, weight of pods per crop and yield per hectare (ton/ha). But the interaction of treatment affects the number of flowers, the number of pithy pods and the weight of 100 seeds.